Exact solutions for the incompressible electrically conducting viscous flow between two moving parallel disks in unsteady magneto hydrodynamic and stability analysis - Balagondar, P.M.; Kempe Gowda, M. (Zielona Góra: Uniwersytet Zielonogórski)
The main interest of the present investigation is to generate exact solutions to the steady Navier-Stokes equations for the incompressible Newtonian viscous electrically conducting fluid flow motion and stability due to disks moving towards each other or in opposite directions with a constant velocity. Making use of the analytic solution, the description of possible conditions of motion is based on the exact solutions of the Navier-Stokes equations. Both stationary and transient cases have been considered. The stability of motion is analyzed for different initial perturbations. Different types of stability were found according to whether the disks moved towards or away from each other.
Keywords: viscous flows; magnetohydrodynamics; stability analysis; Riabouchinsky flow; Hermite`s differential equation